Knowledge and Attitude of Farmers of Small-Scale Dairy Farming at Dhaka, Bangladesh (Global Journal of Science Frontier Research, 2021)
The major purpose of this research study was to determine dairy farmer's knowledge and attitude towards dairy farms and also to explore the relationships between each of 12 selected characteristics of the dairy farmers and their knowledge and attitude towards dairy farming. The study was conducted in 5 Thana's under Dhaka district. The populations of dairy farmers in five Thana's were 182 and sample size was 58 (random sampling method used). An interview schedule was used for data collection. The data were collected during 5 May to 5 August 2019. Scales were developed in order to measure the variables. Majority of the farmers (36.2%) had medium knowledge and 34.5% farmers had low and 29.3% had high knowledge on dairy farming. Regarding attitude, the study showed that about 50% of the respondents had high favorable attitude, 43.1% of the respondents had unfavorable attitude and 6.9% of the respondents had Neutral attitude towards dairy farming.
Keywords: knowledge; attitude; sample size; variables